Chronic Granulomatous Disease: A Rare Hereditary Immuno-deficiency Disorder in a Young Boy with Its Adverse Consequences - Rashid, Mamunur; Nigar, Asfia; Hassan, Md Rashidul (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Chronic granulomatous disease (CGD) is a primary immunodeficiency disease which results from absence of the NADPH oxidase in the professional phagocytic cells neutrophils, monocytes, macrophages and eosinophils. Deficiency of this oxidase renders the patient liable to infection by bacteria and fungi, and, as the name of the disease suggests, to chronic granulomatous inflammation. Here, a young boy presented with increasing breathlessness and productive cough had recurrent episode of pulmonary infection since his childhood. Repeated Chest X-ray and CT scan showed homogenous opacities at different places of lung in different occasions with bilateral reticulo-nodular opacities. Mulipleoraganisms were isolated from sputum at different times. A nitroblu-tetrazolium test (NBT) was done abroad which was positive and confirmed his diagnosis. Since then, He had prophylactic fluconazol and sulphamethoxazoltrimethoprime daily and pneumocaccal and influenza vaccination regularly and proper treatment of acute infective episodes accordingly. In spite all these measures, repeated infection caused grievous harm to his lung leading to irreversible pulmonary fibrosis and bronchiectasis. As a consequence, he became home bound, oxygen dependant and dependant on regular use of long acting bronchodilators in different form. Hematopoeitic stem cell transplantation was advised which was not affordable for his parents. Now, this young boy is waiting for further assaults to his lungs and further deterioration and ultimate hopeless outcomes. J Bangladesh Coll Phys Surg 2015; 33(3): 156-160